Urinary tract infections in pregnancy (review) - N. K. Nikiforovsky; E. A. Stepankova; A. O. Suhorukova (Сибирский научный медицинский журнал, 2020)
Urinary tract infections in pregnancy are common in obstetric practice. This urological pathology is recorded in about every third pregnant woman. There is no trend forward to decline the disease prevalence. Moreover, the number of pregnant women with kidney diseases has increased 4 times over the last 20 years. The best practice for diagnosis of urinary tract infections is urine culture test, which is considered to be the most reliable and accurate diagnostic. According to Order No. 572n by the Ministry of Public Health of the Russian Federation dated 01.11.2012, the procedure is carried out for all pregnant women started from 14 weeks of pregnancy. The necessity for early diagnostics and treatment of urinary tract infections in pregnancy is obvious, since there is a risk of the infection negative impact on a mother and a fetus, course of pregnancy, childbirth and postpartum period. Antibacterial therapy is a method of choice and should be administrated taking into account criteria of safety and tolerability (Food And Drug Administration criteria). Taking into account that antibiotics administration is often empiric, the constant dynamic monitoring of the structure of uropathogens and antimicrobial resistance having specific local features is required.